Estudo sobre raízes alargadas restauradas com pinos de fibra de vidro reembasados com diferentes resinas compostas – Resistência adesiva, caracterização e revisão sistemática com metanálise. - Silva, Camila Ferreira (2020)
Restoration of endodontically treated teeth often requires the use of intraradicular retainers to enable coronary reconstitution, promoting retention of the coronary restoration. Often these posts do not fit properly in roots with wide canals, requiring some customization procedures. This study aims to evaluate different composite resins in the customization and cementation process of fiberglass retainers, through tests of adhesive strength, characterization of materials in association with the retainer and systematic review; specific objective 1: to compare the adhesive strength and failure pattern in the cervical third of glass fiber posts customized with regular composite resin, bulk fill flow resin; specific objective 2: to evaluate the bond strength of glass fiber posts cemented with bulk-fill flow resin in endodontically treated teeth and then compare the results with those of glass fiber posts cemented with resin cement; specific objective 3: to evaluate the degree of conversion, hardness and bond strength by means of micro push-out and pull-out tests of different composite resins when associated with glass fiber posts in roots with increased diameter; specific objective 4: to determine which customization technique has greater fracture resistance and a more favorable failure pattern when associated with glass fiber posts to rehabilitate teeth with enlarged or wide canals. This study has many limitations, however it can be concluded that bulk fill resins can be used as relining material, especially resins of regular consistency and that the use of larger diameter post is essential for the rehabilitation of weakened roots.